Dynamical coupling between a nuclear spin ensemble and electromechanical phonons - Yuma Okazaki (Nature Portfolio, 2018)
Nuclear spins in solids can be implemented into quantum devices but their manipulation usually requires microwave irradiation. Here instead the authors show that they can shift the NMR frequency and drive the nuclear spins into the resolved-sideband regime by using the tunable phonon states from an electromechanical resonator.